THE PRINCIPAL’S STRATEGIES IN ENHANCING COMPETITIVE EDUCATION QUALITY - Wahyudi, Didik (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Competitive educational quality is the key to the success of an educational institution in producing graduates who are able to compete in the era of globalization. The role of the principal is very important in directing and improving the quality of education in schools. School principals must be able to manage school administration well so that educational goals are achieved, as stated by Edward Sallis that the element of leadership is an important aspect of Total Quality Management in the world of education. Therefore, every principal in an educational institution, from primary to secondary level. The principal has an important role in directing as a leader, but does not designate and strengthen the level of leadership integrity. Each educational institution has a different leadership style. Of course, the principal at Al Khairiyah Vocational School has its own leadership style in managing Al Khairiyah Vocational School in order to improve the quality of competitive education. The research method used was a qualitative method by directly interviewing the Principal of Al Khairiyah Vocational School.